Communication Platforms and Perspectives on Climate Change among Layer Farmers in San Jose, Batangas, Philippines - Medina, Benedict O.; A. Hidalgo, Angela Rose; Tabliago, Jhendell A. (International Journal of English Literature and Social Sciences (IJELS), 2019)
Communication plays a vital role in a developing society as it could be used for developing of perspectives. This study aimed to analyze the communication and perspectives on climate change among layer farmers in San Jose, Batangas, Philippines. Descriptive research design in a quantitative approach, along with distributed survey questionnaires to the respondents in the said municipality were utilized to answer the research objectives. Systematic random sampling was used to get the sample size of the layer farmers. Statistical tools such as frequency/percentage, weighted mean and Pearson’s correlation were also used. The layer farmers were greatly exposed in interpersonal communication platforms. Demonstration, meetings, seminars and trainings were of less extent. Radio, television and cellphones were widely used by the layer farmers, while very few had access on the internet. Furthermore, they agreed on food security, water sufficiency, ecological and environmental stability, human security and knowledge and capacity development. However, they moderately agreed on climate-smart industries and services, and sustainable energy. Findings also showed that there is a significant relationship between the layer farmers’ perspectives to the communication platforms they were exposed to.